PREGNANT WOMEN'S KNOWLEDGE ABOUT THE RISK FACTORS OF PREECLAMPSIA IN WADENG VILLAGE, SIDAYU, GRESIK - Yuniarti, Siswari; Wuryaningsih, Sri Hardi; Hanafiyah, Farah (Global Ten Public Health and Nursing Journal, 2023)
Preeclampsia is one of the causes of high maternal mortality rates in Indonesia. Preeclampsia can actually be prevented from causing death in the mother by recognizing the risk factors for preeclampsia. The aim of this study was to identify the knowledge of pregnant women about risk factors for preeclampsia in pregnant women in Wading village, Sidayu, Gresik. This type of research is quantitative with a descriptive design. The population in this study consisted of all 53 pregnant women in Wadeng Village, Sidayu, Gresik. Sample selection used a non-probability sampling technique , namely saturated sampling. The variable in this study was pregnant women's knowledge about risk factors for preeclampsia. Data collection was carried out by asking questions to pregnant women through a questionnaire sheet. Data were analyzed descriptively. The results of this study were obtained from 53 pregnant women, more than half had good knowledge about reproductive factors, more than half had good knowledge about health status factors, more than half had good knowledge about health behavior factors, and most had good knowledge about supporting factors. Pregnant women are expected to increase their knowledge about risk factors for preeclampsia as early detection which is useful for preventing preeclampsia by searching for information in the mass media, being good at sorting information by asking health workers when making ANC visits, utilizing the services of health workers in the village, namely pregnant women's classes, and participating active in classes for pregnant women. Keywords: Knowledge, Pregnant women, Risk factors, Preeclampsia